Remote photoacoustic tomography using diode-array and speckle-analysis - Lengenfelder, Benjamin; Jarkas, Hassan; Shabairou, Nadav; Hohmann, Martin; Schmidt, Michael; Zalevsky, Zeev; Klämpfl, Florian (Proceedings Volume 11363, Tissue Optics and Photonics; 1136308 (2020), 2020)
Photoacoustic imaging is a new, rising imaging technique which combines high penetration depth with a good image contrast. It is demonstrated for the first time that remote photoacoustic sensing by speckle-analysis can be performed in the MHz-sampling range using a low-resolution diode array by showing experimental results. Phantoms and ex-vivo samples are measured in transmission-mode. In addition, the detection sensitivity of the new system is estimated. The new technique might help in future to broaden the applications of photoacoustics in special applications like wound imaging, endoscopy or guiding laser surgerie
Keywords: Photoacoustic; remote sensing; diodes